ANALISIS PADA BUKU DONGENG KARAKTER UTAMA ANAK USIA DINI SETIA DAN JUJUR - Karyani, Runi; Respati, Resa; Sumardi, Sumardi (Universitas Pendidikan Indonesia (UPI), 2021)
This research is based on the importance of planting character values for early childhood. One that can instill character education for early childhood is through fairy tales. Fairy tales have many character values contained in them. Character education needs to be taught from an early age both formally and informally. The object of this research study is a fairy tale book entitled